Effect of unbleached pulp kappa number on the kinetics of chlorine dioxide delignification - Simões, Rogério (2010)
Chlorine dioxide delignification of different unbleached kraft pulps from Eucalyptus globulus, having Kappa numbers of 12 to 18, was studied in the temperature range of 285 K to 358 K. The effect of the unbleached pulp Kappa number on the initial fast phase of delignification was investigated with respect to the depletion factors for Kappa number and chlorine dioxide concentration, as proposed by Barroca et al. Furthermore, the behaviour of the floor lignin content of the pulp, or the floor Kappa number, was analysed within this range. The results show that all pulps exhibit a similar pattern, with respect to temperature, in depletion factors for Kappa number and chlorine dioxide concentration. The degree of normalised delignification and chlorine dioxide consumption is very similar and independent of the Kappa number of the unbleached pulps. Moreover, the results reveal that there is a strong correlation between the floor lignin content and the temperature, and that this correlation is applicable to a wide range of unbleached pulp Kappa numbers, since the residual Kappa number is independent of its initial value. The results enable the general application of a kinetic model to kraft pulps with different unbleached Kappa numbers.